Characterization biodegradable film of ginger nanofiber renvorced PVA bionanocomposites. Issue 1 (1st November 2022) - Ariksa, J; Suhdi,; Setiawan, Y; Saparin,; Wijianti, E S; Wibowo, B S; Yandi, W
Abstract: The high demand for degradable transparent films with good physical properties and tensile strength has motivated the development of PVA bionano composites reinforced by ginger nanofibers (GF). Cellulose nanofibers are obtained from ginger pulp fibers. This study's objective was to describe the PVA/GF bionano composite films' characteristics. Variations in volume to be used suspension of GF 5, 10 and 15 ml, mixed with PVA gel using ultrasonication. The addition of GF nanofibers into the PVA matrix increased the tensile properties significantly. Bionano composites with 15 ml GF got the best results compared to other volume variations. The film has a 38.5 MPa tensile strength. Meanwhile, the bionano composite films' transparency was marginally decreased by the inclusion of GF nanofibers. These results indicate that bionano composite films of PVA and GF nanofibers have the potential to be developed in food packaging applications.